Integration of PLGA Microparticles in Collagen-Based Matrices: Tunable Scaffold Properties and Interaction Between Microparticles and Human Epithelial-Like Cells. Issue 3 (11th February 2020) - Gallo, L.C.; Madaghiele, M.; Salvatore, L.; Barca, A.; Scialla, S.; Bettini, S.; Valli, L.; Verri, T.; Bucalá, V.; Sannino, A.
Abstract: The feasibility to obtain highly porous collagen-based scaffolds (SCs) integrated with uniformly dispersed poly(lactide-co-glycolide) (PLGA) microparticles (MPs) was evaluated. PLGA-MPs were prepared by double emulsion technique and SCs with different amounts of MPs (SC/PLGA-MPs) were produced. Results showed that SC/PLGA-MPs could be successfully manufactured, the PLGA-MPs being physically retained in the SCs, without affecting the porous structure. PLGA-MPs also increased the SC hydrophilicity, acted as a mechanical reinforcement and retarded the degradation rate. In addition, the interactions between MPs and Caco-2 cells did not interfere with the correct morphological, adhesion and proliferation pathways. GRAPHICAL ABSTRACT: